Case report: concurrent herpesviral and presumptive iridoviral infection associated with disease in cultured shortnose sturgeon, Acipenser brevirostrum (L.), from the Atlantic coast of Canada. Issue 2 (22nd July 2013) - LaPatra, S E; Groff, J M; Keith, I; Hogans, W E; Groman, D
Abstract Approximately 8 weeks after a chlorine insult associated with the city water supply, shortnose sturgeon, Acipenser brevirostrum (L.), from one group presented with small (3–4 mm) irregular foci of cutaneous pallor that involved the dorsocranial integument with progressive ulceration of the nascent lesions. Various bacterial organisms were isolated from the cutaneous lesions, but not from the internal viscera. Histologically, the nuclei of the intralesional and perilesional epidermal cells often exhibited margination of the chromatin that resulted in a homogenous, pale, amphophilic, tinctorial quality of the nucleoplasm consistent with a herpesvirus infection. In addition, rare lamellar epithelial cells were prominently enlarged due to an abundant, dense, basophilic cytoplasm characteristic of an iridovirus infection. Inoculation of cutaneous lesion and kidney, spleen, liver sample pools from affected shortnose sturgeon onto white sturgeon spleen (WSS‐2) cell line induced cytopathic effect characterized by syncytia formation. Ultrastructural analysis of infected WSS‐2 cells revealed viral particles with a characteristic herpesvirus morphology. Intranuclear hexagonal capsids had a diameter of 95–108 nm, and enveloped particles present in the cytoplasm of infected cells had a diameter of 176–196 nm. This is the first report of a herpesvirus and a possible iridovirus‐like infection in shortnose sturgeon.